DRUG MANAGEMENT EVALUATION THROUGH EXPIRED DRUG PROFILE ANALYSIS AT “X” HOSPITAL IN BALI - Kadek Lia Andini; Made Krisna Adi Jaya (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2023)
Background: One of the most important hospital management in the provision of health services as a whole is drug management. Remember the important position of drugs for hospitals; their management must be carried out effectively and efficiently because if they do not, they can have a negative impact on hospitals, both medically, socially and economically. Drug management is crucial in the drug management cycle to determine drug stocks that suit the needs of health services with guaranteed quality and can be obtained when needed. One of drug management is by controlling expired drugs. Medicines that have passed their expiry date can be dangerous because they reduce the stability of the drug and can cause toxic effects. Objective: This study aims to describe drug management in terms of expired drug profiles and determine the factors that influence the number of expired drugs in